Massive entry of BK Polyomavirus induces transient cytoplasmic vacuolization of human renal proximal tubule epithelial cells. - Elias Myrvoll Lorentzen; Stian Henriksen; Christine Hanssen Rinaldo (PLoS Pathogens)
BK polyomavirus (BKPyV) is a ubiquitous human virus that establishes a persistent infection in renal tubular epithelial cells and mainly causes disease in kidney transplant recipients. The closely related simian polyomavirus SV40 is known to cause cytoplasmic vacuolization in simian kidney cells, possibly increasing progeny release and cell death. This study aimed to determine whether BKPyV causes cytoplasmic vacuolization in primary human renal proximal tubule epithelial cells (RPTECs) and to investigate its potential role in the replication cycle. Using a large infectious dose (MOI 100-1000), a fraction of RPTECs (10-72%) showed early-wave vacuolization from 3 hours post-infection (hpi), which was mainly reversed by 36 hpi. Independent of the infectious dose, late-wave vacuolization occurred around the timepoint of progeny release. BKPyV receptor binding and internalization were required, as neuraminidase pretreatment and preincubation or treatment with a BKPyV-specific neutralizing antibody prevented early or late-occurring vacuolization. Microscopy revealed that the vacuoles were enlarged acidic endo-/lysosomal structures (dextran, EEA1, Rab5, Rab7, LAMP1, and/or Lysoview positive) that contained membrane-bound BKPyV. Time-lapse microscopy and quantitative PCR revealed that cell death and progeny release preceded late-wave vacuolization, mainly affecting cells directly neighboring the lysed cells. Thus, vacuolization had little impact on cell death or progeny release. Addition of the V-ATPase inhibitor Bafilomycin A1 at 0 hpi blocked vacuolization and BKPyV replication, but addition at 2 hpi only blocked vacuolization, suggesting that continuous endosomal acidification and maturation is needed for vacuole formation, but not for BKPyV replication. Our study shows that a massive uptake of BKPyV in RPTECs induces transient enlargement of endo-/lysosomes and is an early event in the viral replication cycle. Vacuolization gives no clear benefit for BKPyV and is possibly the result of a transiently overloaded endocytic pathway. Focal vacuolization around lysed cells suggests that the spread of BKPyV is preferably local.